The Effect of Job Satisfaction, Work Motivation and Work Environment on the Performance of PT. Kurnia Abadi Padang - Susanti, Febsri; Candra, MHD Julizarmi (Bina Bangsa International Journal of Business and Management, 2023)
This study aims to determine the effect of job satisfaction, work motivation and work environment on employee performance at PT Kurnia Abadi Padang. This type of research is quantitative research. The sample consisted of 63 employees of PT Kurnia Abadi Padang using total sampling. Analysis of the data used is multiple linear regression analysis, classical assumption test, and hypothesis testing. The results showed that variable job satisfaction and work environment has no effect on employee performance at PT Kurnia Abadi Padang. Work motivation have a positive and significant effect on Job Satisfaction at PT Kurnia Abadi Padang